Electrochemical removal of nitrate from wastewater. Issue 1 (July 2020) - AL-Housni, Mohammed; Hussein, Ameer Hashim; Yeboah, David; Al Khaddar, Rafid; Abdulhadi, Bareq; Shubbar, Ali Abdulhussein; Hashim, Khalid S.
Abstract: There are many natural elements that cause pollution of groundwater and surface water. Nitrate is one of those pollutants that could cause serious problems to the aquatic life and human health. Consequently, environmental organisations and most of the governments around the world limited nitrates in potable water to 50 and 10 mg/L for adults and babies, respectively. The current research explores the removability of nitrate from industrial effluents using an electrochemical cell (ESE). The latter is a laboratory-scale batch flow cell having steel electrodes. The experiments were conducted using nitrates solution having100 mg/L. This investigation also studied the impact distance between the electrodes (SBE), treatment period (TP), current density value (CDV) and the initial pH on nitrates removal. Box-Behnken design technique (BBD) has been utilized to optimize the impacts of TP, CDV, SBE and pH on the removal of nitrates by ESE and also to generate a regression model to simulate the removability of nitrates by the ESE. The results of this investigation indicated that the optimum removal of nitrates was 93.4% that achieved at TP of 60 minutes, SBE of 0.5 cm, CDV of 3 mA/cm 2 and initial pH of 6. Furthermore, the developed model's findings were in a respectable compatibility with the experimental findings (R 2 =0.904). In conclusion, the current investigation indicated that the ESE has good capacity to remove nitrate.